An introduction to airline economics - O'Connor, William E. (Praeger, 2001)
An introduction to the economics of US airline services, both domestic and international. This edition is revised to cover developments and changes in the industry. It includes self-testing questions for each chapter and an appendix covering portions of the basic transportation statute.